Produção da habitação no contexto da fabricação digital: mapeamento do potencial industrial na Região Metropolitana da Grande Vitória - Andrade, Kyle Bussinguer Spínola de (2023)
This research scrutinizes the technologies linked to the digital fabrication of architecture capable of being applied in the production of houses in the Metropolitan Region of Greater Vitória (RMGV), which could contribute to mass customization. To this end, the research analyzes the potential of equipment, means of production in favor of formal diversity and customization of the production of housing architecture in Brazil. The hypothesis raised is that the means of production related to digital fabrication are available in the service trade and could contribute to the production of these dwellings, as in the case of the field study developed in the Metropolitan Region of Greater Vitória, Espírito Santo. This field study has the premise of identifying and delimiting the predisposing companies and equipment in the industry of the investigated region to catalog those that could be used for the manufacture of housing in the respective state. This was done through the identification, mapping and development of a summary table which contains the technologies, their respective uses, the dimensions of the work areas, the municipalities where they are located and the area of operation of the establishments that own the CAD/CAM2 equipment at RMGV. As a complement, an analysis was carried out of the means of production and equipment regarding digital fabrication for the construction of houses in the world and in Brazil, with examples of housing produced with this approach. However, the research revealed that digital fabrication isn´t used for the production of housing as it could´ve, even though industries and services trade provide equipment that uses CAD/CAM technology, as demonstrated in the case of RMGV.